A phenomenological study of the experiences of adolescents following maternal HIV-disclosure - Sibanyoni, Sibongile Success (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
Maternal HIV-disclosure to an adolescent is a controversial issue especially when considering the suitable time and context in which disclosure should take place. Furthermore there have been other considerations such as the adolescent's emotional maturity as well as gender issues which have played a role in regards to determining whether the adolescent would be able to understand and cope effectively post-disclosure. These considerations formed the basis of this study's aim and objectives which primarily focused on taking into account the developmental aspects apparent in the adolescent phase. These include adolescent's relations with their mother, their peers and the meaning attached to having an education and career in their lives. For purposes of this study it was deemed important to actually explore with the adolescent's the meaning they uphold pertaining to maternal HIVdisclosure. This differs from previous research which has focused predominantly on accessing adolescent's experiences via their parents and in particular, their mothers. Data of only three participants was included following in-depth interviews being conducted. Data was analysed via Interpretive Phenomenological Analysis (IPA) which enabled an enhanced understanding and meaningful interpretation of the adolescent's experiences following maternal HIV-disclosure. From the findings it became apparent that most concerns had already been addressed and were similar when compared to previous research that had been conducted. However one notable different finding was that instead of adolescent's acting in ways that would lead to them self-sabotaging their lives they instead portrayed themselves to be living in a responsible manner. It became apparent rather that it was the adolescent's mother rather that became more inclined to engage in self-sabotaging behaviours.
Keywords: HIV infections -- Transmission -- South Africa -- Grahamstown; HIV-positive youth -- South Africa -- Grahamstown; Teenagers -- Diseases -- South Africa -- Grahamstown; HIV infections -- Social aspects -- South Africa -- Grahamstown